Penggunaan Status Whatsapp Sebagai Digital Marketing Warga Kecamatan Medan Satria Bekasi Di Era New Normal - Dessy Andamisari (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
Social media can be used as one of the digital marketing media that is quite effective in business activities in all lines, including small home businesses during the Covid-19 pandemic and the PSBB policy that changes new lives (new normal). It is important to note that each social media has its own characteristics. For this reason, digital marketing efforts through social media need to be designed and adapted to the characteristics of each social media first. This study aims to analyze the advantages and disadvantages of using WhatsApp status as a digital marketing medium. Using a qualitative approach with a phenomenological approach. The subjects of this research are residents of Medan Satria Bekasi District, while the object of this research is WhatsApp status which has various supporting features as a digital marketing media. The results of the study conclude that although there are many conveniences and advantages that residents of Medan Satria District can take advantage of using WhatsApp Status as a digital marketing medium, also has drawbacks that need special attention if you want your business to develop and achieve greater profits. Thus, if you want to do massive marketing activities, then WhatsApp Status is not the right choice.